Plumbing leakage detection system with water level detector controlled by programmable logic controller type Omron CPM2A - Sri Hartanto; Desmayadi Desmayadi (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2022)
There is a chance of leakage in the plumbing caused by water pressure in the pipes, improper installation of pipe connections, or external influences, such as earthquakes. Plumbing leakage that is detected too late can cause damage to other systems. It is necessary to have a plumbing leakage detection system to detect a leak in the plumbing. Therefore, in this research, a plumbing leakage detection system is designed with a water level detector (WLD) controlled by a programmable logic controller (PLC) type Omron CPM2A. The method used in this research is designing the optimal model form of the system, which is distinguished by designing hardware and software, testing the devices, such as power supply, WLD, and channel relay module (CRM), and making conclusions. From the results of this research, it was found that the system works well in detecting leakage of plumbing, as indicated by all transistors' ability to work well where the electrodes (E1 and E2) are connected by water. The transistor in the WLD module will work as a switch or transistor in the saturation position. In this research, it can be seen that even though there is a leakage from the relay contacts of 1.8 VDC, it is still considered in a safe condition because to provide a trigger to the 3B3D Module, a minimum of 12 VDC is required. In addition, when the relay is not working or off, the measurement at the normally closed (NC) terminal is 12 VDC.